2016
DOI: 10.1186/s12891-016-1340-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in load carriage injuries of Australian army soldiers

Abstract: BackgroundWith the removal of gender restrictions and the changing nature of warfare potentially increasing female soldier exposure to heavy military load carriage, the aim of this research was to determine relative risks and patterns of load carriage related injuries in female compared to male soldiers.MethodsThe Australian Defence Force Occupational Health, Safety and Compensation Analysis and Reporting workplace injury database was searched to identify all reported load carriage injuries. Using key search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
1
15
3
Order By: Relevance
“…The gender equality in service-related injuries that we observed in our study is contradictory to previous military research [54, 55]. We did not have the data to conclude whether the two genders had distinct positions or were assigned to different tasks and operations in the military, which could influence service-related injuries.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The gender equality in service-related injuries that we observed in our study is contradictory to previous military research [54, 55]. We did not have the data to conclude whether the two genders had distinct positions or were assigned to different tasks and operations in the military, which could influence service-related injuries.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not have the data to conclude whether the two genders had distinct positions or were assigned to different tasks and operations in the military, which could influence service-related injuries. Furthermore, we combined several types of injuries into a broad and heterogeneous variable, potentially masking gender differences in injuries at certain anatomic locations [54, 56]. However, inconsistent results on the gender-specific risks of sustaining an injury in the military could reflect crucial differences between nations in military selection, training, equipment, health care, or in symptom reporting [5759].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Lyons, et al [ 34 ] found that the majority of studies in law enforcement contexts that have investigated injuries included only male participants. Understanding differences in injury presentations between male and female officers is of importance as research has shown that, for examples, male and female tactical personnel can suffer from different lower limb musculoskeletal injuries [ 35 ] and that lower limb interventions to address gender-specific injuries are effective [ 36 ]. Furthermore, the review found that there were no standard injury definitions, with many of the included studies failing to include any definition at all [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As with other tactical occupations where load carriage is a requirement, such as in law enforcement (10 to 22 kg [4,5]) and the military (up to 45+ kg [6,7]), the loads carried by firefighters can increase their risk of physical injuries [8]. These injuries range from neurological injuries (like meralgias and brachial plexus palsy [9,10]) to the more typical musculoskeletal injuries (like sprains, strains, and fractures [11,12]). Furthermore, for the firefighter, carrying these loads can increase their risk of a slip, trip or fall when conducting fire suppression tasks in urban environments [13].…”
Section: Introductionmentioning
confidence: 99%